Relationship between diet health quality and the level of functional fitness and quality of life among Polish women aged 60+ - Maria Krystyna Gacek; Agnieszka Wojtowicz; Grażyna Kosiba; Magdalena Majer; Joanna Gradek; Olga Czerwińska-Ledwig (Roczniki Panstwowego Zakladu Higieny, 2025)
Background Healthy lifestyle is a key factor in improving health and quality of life at any stage of ontogenesis.